SHARIA INVESMENT MODEL AND SHARIA BALANCE SHEET WITH MONTI KLEIN METHOD - INAYATUL GHAIDA (NIM: 10113071), NIDYA
Currently sharia banking is developing in Indonesia. The profit-sharing system in this banking helps Muslims to avoid the interest applied by conventional banks. However, there are still many Muslims who do not know this banking system. Therefore, this Final Project will examine two topics about the application of mathematics in shariah banking to determine the sharia investment applied to traders in Balubur Market and determine the Monti Klein’s profit and loss in five Islamic banks in Indonesia. In sharia investment, the daily income data from the traders after being given a loan will be used to calculate the profit-sharing portion for traders and investors using moneylender system and sharia investment system. These results will be used to determine the sharia optimization model so that they can obtain optimal profit sharing portion. In Monti Klein's profit and loss, the variables in the Monti Klein equation are derived from the existing report data on the Financial Services Authority (OJK) website and the calculation data are derived from the simple model construction of the sharia bank balance sheet to determine the funding, financing and equivalent rate. The Monti Klein’s profit and loss will be projected for 12 months ahead with decomposition method. The results of both studies show that these two topics can be used to explain the current state of shariah banking in Indonesia. It is expected that this Final Project can provide knowledge for the community about sharia banking.